Experience Disclosing Mental Health Conditions Among College Students from Different Ethnic Backgrounds - Hampole, Shilpa R.; Nguyen, Steven H. S.; Woodhead, Erin L. (Building Healthy Academic Communities Journal, 2019)
Aim: The current study compared disclosure of mental health problems to staff, faculty, and peers among college students from different ethnic backgrounds. Background: Although there are differences in mental health stigma between college students from different ethnic backgrounds, there is limited research on whether these differences are associated with negative experiences disclosing mental health conditions on campus. Methods: The sample (N = 66) was 71% female; average age was 19.03 years (SD = 1.14). Participants identified as Latino/a (35.4%), Asian American (33.8%), Caucasian (13.8%), or other/mixed ethnicity (16.9%). Results: For disclosure to staff, there was a main effect of ethnicity. Post-hoc analyses found that Latino/a students were significantly more comfortable disclosing mental health problems to staff than Asian American students. There were no significant effects for disclosure to faculty or peers. Conclusions: This preliminary study suggests that universities must optimize outreach and mental health services for different ethnic groups to improve campus experience around mental health conditions.